Swimming or Drowning in the Depths of Partnership. Issue 3 (September 2017) - Sturup, Sophie
Abstract: This exploratory research paper seeks to consider the problems that may arise in the process of creating deep and lasting partnerships in public‐private partnerships (PPPs). It does this by contrasting two case studies of very different PPPs, Copenhagen's metro project and Melbourne City Link. The paper puts forward the case for the author's concern that a deep partnership could lead either to mercantile government or quasi‐governmental private parties and thus lead to a diminution of the benefits of PPPs. The paper concludes that these concerns are relevant and need to be considered and guarded against no matter the contract conditions. Abstract : This paper considers problems which may arise in deepening partnerships in PPPs. The paper is concerned that a deep partnership could lead to mercantile government, or quasi‐governmental private parties and diminish the benefits of PPPs. The paper concludes that these concerns need to be considered and guarded against in PPPs.